The calculus of disclosure of HIV seropositive status: experiences of HIV positive pregnant women at Bonda Mission Hospital, Manicaland, Zimbabwe - Maphosa, Sibangilizwe (Unknown, 2016)
Disclosure can be capable of motivating the other partner to seek testing for their HIV status. As a result this may start a chain of reaction that can lead to behavioral change, like embarking on safe sex to prevent re-infection with another strain of HIV. HIV status disclosure has been a daunting task for pregnant women; several studies have shown that most break-ups of marriages, loss of shelter, relationships or even death, suicides are some of the calamities that most women encounter when they disclose. The study therefore explores the factors that make disclosure a daunting task for pregnant women. Methods: A phenomenological research design was used in order to understand the factors that influence disclosure of seropositive status results among pregnant women. The study focused on HIV positive pregnant women aged 18-30 years from Bonda Mission Hospital. Ten participants were purposively selected for in-depth semi-structured interviews and thematic analysis was used. Results: The study revealed that status disclosure is a daunting task for pregnant women, fear of reaction by husbands, family and children, loss of financial support, stigma, accusation of infidelity and abandonment are the major challenges for HIV positive pregnant women when considering the calculus of disclosure. Conclusions and recommendations: Family rejection and stigma were the major challenges affecting the disclosure of HIV seropositive status. HIV/AIDS is still a misunderstood phenomenon and considered as a shame and embarrassment, hence the stigma. There is need for vigorous and deliberate education for the individuals both HIV positive and negative, families and the society at large on HIV/AIDS issues.